2014
DOI: 10.1002/hed.23765
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck squamous cell carcinoma lymphatic spread and survival: Relevance of vascular endothelial growth factor family for tumor evaluation

Abstract: Although lymphatic spread is a significant event in the progression of HNSCC, the expression of VEGF-C, VEGF-D, and VEGFR3 does not correlate with clinicopathological characteristics, suggesting that other signaling pathways mediate lymphangiogenesis in HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…At present, studies have found that tobacco and alcohol are important factors in inducing HNSCC (Jethwa & Khariwala, 2017;Kawakita & Matsuo, 2017). The incidence of HNSCC is also relatively high in the world, which not only directly affects patients' breathing, eating and language functions, but also causes rapid growth of neck lymph node metastasis with the help of abundant blood supply and lymphatic refluence (De Sousa et al, 2015). The main clinical treatment methods for HNSCC include surgery, radiotherapy and chemotherapy (Cramer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…At present, studies have found that tobacco and alcohol are important factors in inducing HNSCC (Jethwa & Khariwala, 2017;Kawakita & Matsuo, 2017). The incidence of HNSCC is also relatively high in the world, which not only directly affects patients' breathing, eating and language functions, but also causes rapid growth of neck lymph node metastasis with the help of abundant blood supply and lymphatic refluence (De Sousa et al, 2015). The main clinical treatment methods for HNSCC include surgery, radiotherapy and chemotherapy (Cramer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…20 Although it is not yet clear which of peritumoral 21 or intratumoral lymphatic vessel density [22][23][24][25] is more relevant for the development of lymph node metastasis, a great number of studies have shown a significant association between lymphatic vessel density and lymph node metastasis in HNSCC, mostly using antibodies against podoplanin or the anti-hyaluronan receptor LYVE-1. 29 In this study, we used a specific antibody against the transcription factor Prospero homeobox protein 1 (PROX1) as an indicator of lymphatic vessel density. 29 In this study, we used a specific antibody against the transcription factor Prospero homeobox protein 1 (PROX1) as an indicator of lymphatic vessel density.…”
Section: Introductionmentioning
confidence: 99%
“…23,[25][26][27][28] However, the use of disparate assessment methods across studies make it difficult to draw definitive conclusions on the use of lymphatic vessel density as a predictor of lymph node metastasis. 29 In this study, we used a specific antibody against the transcription factor Prospero homeobox protein 1 (PROX1) as an indicator of lymphatic vessel density. Its specific lymphatic endothelial cells nuclear staining 30 allows for precise quantification of lymphatic vessels without the risk of misinterpretations from morphological pitfalls and/or unspecific staining.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that high MVD is associated with both metastasis and poor prognosis in patients with head and neck cancers . Lymphatic vasculature has also been shown to play a role, with high LVD being associated with poor prognosis in gastric, non‐small‐cell lung, and head and neck cancers . Many of these studies have distinguished between peritumoral and intratumoral vessel densities.…”
Section: Discussionmentioning
confidence: 99%
“…9,22 Lymphatic vasculature has also been shown to play a role, with high LVD being associated with poor prognosis in gastric, non-small-cell lung, and head and neck cancers. 10,11,[23][24][25][26][27][28] Many of these studies have distinguished between peritumoral and intratumoral vessel densities. In HNSCC, high intratumoral LVD has been reported to be associated with higher risk of local recurrence, 10 cervical nodal metastases, 11,29 and worse overall survival.…”
Section: Discussionmentioning
confidence: 99%